EFFECT OF A VARIOUS OF COMBINATIONS OF PLANTING MEDIA AND DOSES OF NPK FERTILIZER ON THE GROWTH OF THE TURMERIC RHYMPANG (Curcuma domestica Val.) - Nurhayati, Dewi Ratna; Alhaffiz, Hannugra Essa (Institute of Computer Science (IOCS), 2023)
The Effect of Various Combinations of Planting Media and NPK Fertilizers on Turmit Tolman Growth This research was conducted on food and horticultural crops. Colomadu Karanganyar December 2022 Essay March 2023. The aim of the study was to determine the effect of different culture media and doses of npk fertilizer on the growth of lymph turmite (curreal domestica val) and look for the composition of the plant media (curreal domestica val.) which is good for the growth of turmeric. This study used a completely randomized design (CRD) consisting of two factors. The first factor to give a variety of plant media (M) consisting of 4 degrees (M0) soil (control), (M1) ground + rice chaff, (M2) soil + charcoal rice chaff, (M3) soil + cocopeat. The second factor is npk (n) fertilization consisting of 4 degrees (N0) without dose (0 g / plant ), (N1) 150kg / ha (5.39 g / plant ), (N2) 200 kg / ha ( 7.19 g / plant ), ( N3 ) 250 kg / ha ( 8.99 g / plant ). Observation data in the analysis using a range of footprint analysis (anova) and continued with a bnj test at a rate of 5%. The results of the study showed that 1) The treatment of planting media has a significant effect on the observation of the wet weight of the stalk, but has no significant effect on plant height, number of leaves, wet weight of rhizomes 2) The treatment of NPK fertilizer has a significant effect on plant height, number of leaves, wet weight of stalks, wet weight of rhizomes 3) The interaction between treatments has a significant effect on the number of leaves, but has no significant effect on plant height, wet weight of stalks, wet weight of rhizomes.